Hubungan Tipe-Tipe Obesitas dengan Hipertensi pada Usia Dewasa Muda di Indonesia: Hubungan Tipe-Tipe Obesitas dengan Hipertensi pada Usia Dewasa Muda di Indonesia - Rumaisyah, Rumaisyah; Fatmawati, Iin; Ayu Arini, Firlia; Octaria, Yessi Crosita (Amerta Nutrition, 2023)
Background: Hypertension is the dominant risk factor for coronary heart disease, the first cause of death in Indonesia. The prevalence of hypertension in Indonesia based on blood pressure measurements reached 34.11% in 2018. An increase the prevalence and risk of hypertension occurs in young adults with obese, both obesities based on body mass index and abdominal circumference as a parameter. Objectives: To analyze the association between types of obesity and hypertension in young adults in Indonesia. Methods: Cross-sectional study used secondary data from Indonesia National Basic Health Research 2018. Individuals aged 25-44 years, measured blood pressure for 3 times, had complete data, and not pregnant were included in this study (35,258 participants). Univariate and bivariate analysis used chi-square and then logistic regression test as multivariate analysis. Both used α 0.05 and 95% confidence interval. Results: Based on logistic regression, hypertension has a significant correlation with general obesity, abdominal obesity, combined obesity, age, gender, education, employment status, physical activity, smoking status, and fruit and vegetable consumption levels. In addition, the probability of developing hypertension based on the type of obesity is the largest in combined obesity, then general obesity and abdominal obesity with adjusted odds ratio 3,50; 1,87; and 1,79. Conclusions: General obesity, abdominal obesity, and combined obesity were associated with hypertension in young adults in Indonesia. Body mass index measurement combined with abdominal circumference can be a parameter of three types of obesity and a predictor of hypertension.